Analisis Pengendalian Biaya Kualitas Dalam Menunjang Efektivitas Produksi Pada PT. Galatta Lestarindo - Vin Sen; Sunarji Harahap; Elidawati Elidawati; Thomas Sumarsan Goh (Journal of Economic, Bussines and Accounting (COSTING), 2022)
Galatta Lestarindo is a company engaged in the production of Dolomite fertilizer which was established in 1992, where the quality costs incurred by the company have not been able to reduce the level of product damage. The purpose of this research is to analyze quality cost control in supporting the effectiveness of production at PT. Galatta Lestarindo. Analysis of the data used is descriptive analysis. The total population of this study was 340 employees with the sampling technique using the Slovin formula so that from the calculations obtained as many as 184 samples. Data collection techniques are observation, interviews and literature. Based on the results of the quality cost control analysis conducted by the company, it appears that the quality cost control carried out by the company has not met the quality standards set by the company to increase production effectiveness, because the quality costs incurred by the company are greater than the quality standards that have been set. Keywords: Quality Cost Control, Production Effectiveness